The Effect of Aggregation of Accounting Information via Segment Reporting on Accounting Conservatism" - Steele,Logan; Bens,Daniel; Monahan,Steven (European Accounting Review, 2018)
In a sample of US multiple-segment firms, we document a negative association between aggregation via segment reporting and timely loss recognition. A higher level of aggregation, as reflected in a firm’s reported organizational structure (the definition and characteristics of its segments), causes a multiple-segment firm to exhibit less cross-segment variation in profitability than a matched control portfolio of single-segment firms. We find that firms that engage in more aggregation report accounting numbers that provide less timely information about economic losses. We also observe that firms that provide more disaggregated segment data subsequent to adopting SFAS 131 experienced an increase in timely loss recognition. This result implies that higher quality segment reporting leads to an increase in timely loss recognition, which, per extant research, is associated with better governance.
Keywords: Accounting